Capital flows and macroprudential policies: A multilateral assessment of effectiveness and externalities - John Beirne; Christian Friedrich (Bank of Canada, 2014)
This paper assesses the effectiveness and associated externalities that arise when macroprudential policies (MPPs) are used to manage international capital flows. Using a sample of up to 139 countries, we examine the impact of eight different MPP measures on cross-border bank flows over the period 1999-2009. Our panel analysis takes into account the structure of the banking system as well as the presence of potential crosscountry and cross-asset class spillover effects. Our results indicate that the structure of the domestic banking system matters for the effectiveness of MPPs. We specifically find that a high share of non-resident bank loans in the MPP-implementing country reduces the domestic effectiveness of most MPPs, while a high return on assets in the domestic banking system has the opposite effect. Our results on the spillover analysis indicate that both types of spillover can occur. First, we find that a high return on assets in the banking system of countries other than the MPP-implementing one leads to a reduction, and a greater degree of trade integration leads to an increase in spillovers across countries. However, the economic significance of the results suggests that only a limited number of countries will tend to experience substantial geographical spillover effects. Second, we also find some evidence of spillover effects across asset classes within countries. – – Nous évaluons l'efficacité des politiques macroprudentielles dans la gestion des flux de capitaux internationaux et les externalités découlant de leur mise en oeuvre. À l'aide d'un échantillon comptant jusqu'à 139 pays, nous étudions les effets de huit mesures de politique macroprudentielle sur les flux bancaires transfrontaliers au cours de la période allant de 1999 à 2009. Notre analyse longitudinale examine la structure du système bancaire et la présence de possibles effets de débordement entre pays et entre categories d'actifs. Nos résultats indiquent que la structure du système bancaire national a une incidence sur l'efficacité des politiques macroprudentielles. Plus précisément, nous constatons qu'une proportion élevée de prêts accordés par des banques non residents dans un pays qui adopte des politiques macroprudentielles réduit l'efficacité à l'échelle intérieure de la plupart de celles-ci, alors qu'un haut rendement des actifs dans le système bancaire national a une incidence contraire. Par ailleurs, notre analyse donne à penser que les deux types d'effets de débordement peuvent se produire. Premièrement, nous observons qu'un haut rendement des actifs dans le système bancaire de pays autres que celui qui applique des politiques macroprudentielles entraîne une diminution de ces effets, alors qu'un niveau élevé d'intégration commerciale au sein du même groupe de pays provoque une hausse dans tout le groupe. Cependant, le fait que les résultats soient économiquement significatifs tend à indiquer que généralement seul un nombre limité de pays subit des effets de débordement géographiques. Deuxièmement, certains résultats laissent entrevoir des retombées touchant diverses catégories d'actifs à l'intérieur de pays.
Keywords: F3; F5; G01; G11; 330; International topics; Financial markets; Balance of payments and components